The Effectiveness of Use of Digital Learning Media on Student Creativity in Citizenship Education Subjects - Tobing, Minar Trisnawati; Sibarani, Imelda Sabrina; Butar-Butar, Zelonika (PT Inovasi Pratama Internasional, 2024)
Teachers are actors who really influence the educational process, because they are at the forefront of the teaching and learning process. Teaching and learning activities have several components such as objectives, materials, methods of teaching and learning activities, tools and learning resources. One of the most influential aspects in the teaching and learning process is learning media. With the current technological developments, teachers find it easier with the emergence of various interesting learning media, one of which is Digital Learning Media. There are several problems found in the world of education, especially at the elementary school level in Indonesia, such as the low ability of students to understand concepts, low student learning outcomes and low student motivation to learn. Other problems are also expressed in other research which suggests the use and utilization of learning media in elementary schools. it's still not done optimally.